The Teknik Pengempukan Daging Ayam Petelur Afkir Menggunakan Ekstrak Buah Nanas dan Pemanfaatannya sebagai Media Pembelajaran - Virahmi Virahmi; Abdul Hakim Laenggeng; Masrianih Masrianih (Media Eksakta, 2022)
This research is an experimental study with a completely randomized design (CRD). Determination of tenderness and pH in rejected laying hens using different concentrations of pineapple extract using Anova data analysis in the SPSS 21 program, then continued with the LSD test. The result of the study obtained different levels of tenderness, pH in rejected laying hens usingdifferent concentrations of pineapple extract. The highest level oftenderness was found in the T3 treatment (25 g + 30 ml) which was0.442%. The lowest level of tenderness was found in treatment T0 (25 g) which was 0.382%. The highest pH content was found in the T0 treatment (25 g + 30 ml) which was 4.71%. The result of the Flipbook E-Modul test based on content expert validator and media experts are suitable for us as learning media with a percentage of 70% and 74%, according to design expert and students validator are very suitable to be used with a percentage of 83.64%, 85.75%, while the average the overall average by content, design, media and student groups is appriate of 78.38%.